Wireless power transmission - exploring source to load inductive link under resonance and varying load condition - Ahmed, Kafeel J.; Zainal, Nur Izzati; Hafiz, Sabihul; Mizan, R.; Khan, Sheroz; Nordin, Anis Nurashikin (IEEE, 2017)
Wireless Power Transmission for powering up of the electronic gadgets, electric vehicles, and biomedical implants is being researched heavily these days. It has been proving to be the only in the electric vehicles battery charging systems, as it is hassle free, more efficient and easy to install. In many-to-one as well in one-to-many power transfer selective resonant technique plays a vital role. The many-to-one principle is mainly in the battery charging system of electric vehicles. This paper explores the source-to -load-coil (one -toone and one-to-two) links using the magnitude of the reflective impedance (ZRef) as a parameter estimating the power transfer efficiency. The analytic expressions and simulation results have been explored in this analysis, showing the effect of resonant and load matching.